Preterm Gut Microbiome Depending on Feeding Type: Significance of Donor Human Milk - Parra-Llorca, Anna; Gormaz, María; Alcántara, Cristina; Cernada, María; Nuñez-Ramiro, Antonio; Vento, Máximo; Collado, Maria C. (Frontiers in Microbiology, 2018)
Preterm microbial colonization is affected by gestational age, antibiotic treatment, type of birth, but also by type of feeding. Breast milk has been acknowledged as the gold standard for human nutrition. In preterm infants breast milk has been associated with improved growth and cognitive development and a reduced risk of necrotizing enterocolitis and late onset sepsis. In the absence of own mother’s milk, pasteurized donor human milk could be the best available alternative due to its similarity to the former. However, little is known about the effect of donor human milk upon preterm microbiota and potential biological implications. Our objective was to determine the impact of donor human milk upon preterm gut microbiota admitted in a referral neonatal intensive care unit (NICU). A prospective observational cohort study in NICU of 69 neonates <32 weeks of gestation and with a birth weight ≤1.500 g was conducted. Neonates were classified in 3 groups according to feeding practices consisting in own mother’s milk, donor human milk or formula. Fecal samples were collected when full enteral feeding (defined as ≥150 cc/kg/day) was achieved. Gut microbiota composition was analyzed by 16S rRNA gene sequencing. Despite the higher variability, no differences in microbial diversity and richness were found, although feeding type significantly influenced the preterm microbiota composition and predictive functional profiles. Preterm infants fed mother’s own milk (MOM) showed a significant greater presence of Bifidobacteriaecae and lower of Staphylococcaceae, Clostridiaceaea and Pasteurellaceae compared to preterm fed donor human milk (DHM). Formula fed Microbial profile was different to those observed in preterm fed own mother’s milk. Remarkably, preterm infants fed donor human milk showed closer microbial profiles to preterm fed own mother’s milk. Inferred metagenomic analyses showed higher presence of Bifidobacterium genus in mother’s milk group was related to enrichment in the Glycan biosynthesis and metabolism pathway that was not identified in the donor human milk or in the formula fed groups. In conclusion, DHM favors an intestinal microbiome more similar to MOM than Formula despite the differences between MOM and DHM. This may have potential beneficial long-term effects on intestinal functionality, immune system, and metabolic activities.